Value Added Tax (VAT) Objects in Digitalization Era: A Juridical Historical Study in Indonesia - Sipayung, Bonarsius; Arsal, Yon; Hamzah, Muhammad Zilal (Scientia Integritas Utama, 2023)
The digitalization era has raised tax avoidance and tax evasion challenges which affect the value added tax (VAT) ratio in Indonesia. Based on normative juridical studies, this study produces 2 (two) conclusions. First, the VAT objects in the prevailing VAT law in Indonesia, which had undergone 5 (five) changes from 1983 to 2021, have not yet regulated several VAT objects in the digitalization era. It can be seen from the potential for tax avoidance and tax evasion in the digitalization era. Second, reformulation of ideal VAT objects in digitalization era in Indonesia can be carried out by expanding the scope of VAT objects based on developments in taatbestand. The tax authority in Indonesia, namely the Directorate General of Taxes, needs to consider expanding the VAT object by applying the certainty principle and comparing it with the provisions in several other countries, such as Singapore, Switzerland and Russia.